OCIAD1 is a host mitochondrial substrate of the hepatitis C virus NS3-4A protease - Tran, Huong T. L.; Dao Thi, Viet Loan (PLOS ONE, 2020)
The hepatitis C virus (HCV) nonstructural protein 3-4A (NS3-4A) protease is a key component of the viral replication complex and the target of protease inhibitors used in current clinical practice. By cleaving and thereby inactivating selected host factors it also plays a role in the persistence and pathogenesis of hepatitis C. Here, we describe ovarian cancer immunoreactive antigen domain containing protein 1 (OCIAD1) as a novel cellular substrate of the HCV NS3-4A protease. OCIAD1 was identified by quantitative proteomics involving stable isotopic labeling using amino acids in cell culture coupled with mass spectrometry. It is a poorly characterized membrane protein believed to be involved in cancer development. OCIAD1 is cleaved by the NS3-4A protease at Cys 38, close to a predicted transmembrane segment. Cleavage was observed in heterologous expression systems, the replicon and cell culture-derived HCV systems, as well as in liver biopsies from patients with chronic hepatitis C. NS3-4A proteases from diverse hepacivirus species efficiently cleaved OCIAD1. The subcellular localization of OCIAD1 on mitochondria was not altered by NS3-4A-mediated cleavage. Interestingly, OCIAD2, a homolog of OCIAD1 with a cysteine residue in a similar position and identical subcellular localization, was not cleaved by NS3-4A. Domain swapping experiments revealed that the sequence surrounding the cleavage site as well as the predicted transmembrane segment contribute to substrate selectivity. Overexpression as well as knock down and rescue experiments did not affect the HCV life cycle in vitro, raising the possibility that OCIAD1 may be involved in the pathogenesis of hepatitis C in vivo.
Gesehen am 26.10.2020